2001
DOI: 10.1385/abab:91-93:1-9:341
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Neural Network Algorithm for On-Line State Inference That Accounts for Differences in Inoculum of Cephalosporium acremonium in Fed-Batch Fermentors

Abstract: One serious difficulty in modeling a fermentative process is the forecasting of the duration of the lag phase. The usual approach to model biochemical reactors relies on first-principles, unstructured mathematical models. These models are not able to take into account changes in the process response caused by different incubation times or by repeated fedbatches. To overcome this problem, we have proposed a hybrid neural network algorithm. Feedforward neural networks were used to estimate rates of cell growth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The application of hybrid semi-parametric models in form of a soft-senor is very attractive for monitoring and both parallel (Lee et al, 2005) and serial (Boareto et al, 2007;Gnoth et al, 2008;Henneke et al, 2005;James et al, 2002;Jenzsch et al, 2007;Psichogios & Ungar, 1992;Schubert et al, 1994a;Silva et al, 2000Silva et al, , 2001von Stosch et al, 2011b) hybrid semi-parametric models find application. It was shown that the performance of a model in which the states and parameters were estimated by Nonlinear Programming (NLP) optimization or Extended Kalman Filter (EKF) approaches was inferior to the performance of a model in which the variable parameters were estimated using neural networks (Psichogios & Ungar, 1992), namely a hybrid semi-parametric model.…”
Section: Soft-sensor -Predictor Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of hybrid semi-parametric models in form of a soft-senor is very attractive for monitoring and both parallel (Lee et al, 2005) and serial (Boareto et al, 2007;Gnoth et al, 2008;Henneke et al, 2005;James et al, 2002;Jenzsch et al, 2007;Psichogios & Ungar, 1992;Schubert et al, 1994a;Silva et al, 2000Silva et al, , 2001von Stosch et al, 2011b) hybrid semi-parametric models find application. It was shown that the performance of a model in which the states and parameters were estimated by Nonlinear Programming (NLP) optimization or Extended Kalman Filter (EKF) approaches was inferior to the performance of a model in which the variable parameters were estimated using neural networks (Psichogios & Ungar, 1992), namely a hybrid semi-parametric model.…”
Section: Soft-sensor -Predictor Methodsmentioning
confidence: 99%
“…Gupta et al (1999) applied two parallel ANNs, each of which inferring a variable value, in series with three other parallel ANNs, each of which estimating a quantity that enters as an input to the mechanistic model. In Gnoth et al (2008), Silva et al (2000Silva et al ( , 2001) the prediction of one central kinetic rate (usually the specific biomass growth rate) by a first ANN, was used as an input (beside others) to another ANN, which in turn predicts another rate, e.g. the product formation rate.…”
Section: Nonparametric Models For Specific Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Syu and Tsao7 employed a NN to model the batch growth of Klebsiella oxytoca . Silva et al 37, 38 used a hybrid NN model to infer the cellular growth and product formation during production of cephalosporin C. A comparative study was performed by James et al 9 for a poli hidroxi butirate (PHB) fed‐batch fermentation process. They compared a feedforward NN, a radial basis function neural network (RBFNN), and hybrid models using either feedforward NNs or RBFNNs.…”
Section: Theoretical Basismentioning
confidence: 99%
“…In this study, we introduce a training strategy, which is similar to applying a neural network design for a state estimator (Linko et al, 1997;Silva et al, 2001), to determine the tunable parameters. Fig.…”
Section: On-line Estimationmentioning
confidence: 99%